Analisis Pemberdayaan Sumber Daya Desa sebagai Desa Pariwisata di Kecamatan Paciran Kabupaten Lamongan - Rohmah, Dian Fatihatur; Harianto, Sugeng (Jurnal Pemberdayaan Masyarakat, 2023)
Indonesia is the largest archipelagic country which makes it the world's maritime axis. Indonesia is a country that has the largest archipelago in the world and a wide and strategic coastline. Paciran District, Lamongan is one of the areas that has a long beach. Village tourism is the utilization of existing resources in the village as tourism that provides benefits to the surrounding community. This study used a qualitative research method with a descriptive approach. This study used primary data and secondary data. The primary data was obtained from observations and interviews with several residents of the Kec. Paciran, Lamongan, while secondary data was obtained from reading some information through several reading sources such as journals, books, etc. This study aims to analyze the empowerment of village resources as a tourism village in Paciran sub-district, Lamongan. The results of this study indicate that Paciran District, Lamongan has many tours that can be visited by tourists ranging from Lamongan marine tourism, Maharani Zoo Lamongan, Wali's graves, to the beach.